Role of Positron Emission Tomography-Computed Tomography Scan in Reaching Definite Diagnosis in Patients With Fever of Unknown Origin and Inflammation of Unknown Origin in Rheumatology Outpatient Clinic - Koreli UY; Torun ES; Adaş M (Open Access Rheumatology: Research and Reviews)
Umut Yılmaz Koreli,1 Ege Sinan Torun,2 Mine Adaş3 1University of Health Sciences, Prof. Dr. Cemil Taşçıoğlu City Hospital, Department of Internal Medicine, Istanbul, Turkey; 2University of Health Sciences, Prof. Dr. Cemil Taşçıoğlu City Hospital, Department of Internal Medicine, Division of Rheumatology, Istanbul, Turkey; 3University of Health Sciences, Prof. Dr. Cemil Taşçıoğlu City Hospital, Department of Internal Medicine, Division of Endocrinology, İstanbul, TurkeyCorrespondence: Ege Sinan Torun, University of Health Sciences, Prof. Dr. Cemil Taşçıoğlu City Hospital, Department of Internal Medicine, Division of Rheumatology, Kaptan Paşa, Darülaceze Cd. No: 27, Şişli/İstanbul, 34384, Turkey, Tel +90 212 314 55 55 ; +90 537 229 17 99, Email egesinantorun@hotmail.comIntroduction: Patients with fever of unknown origin (FUO) and/or inflammation of unknown origin (IUO) challenge clinicians in daily rheumatology practice. Positron emission tomography-computed tomography (PET/CT) is being used in the diagnostic workup of patients with FUO and/or IUO. This study aims to evaluate the clinical utility and diagnostic performance of PET/CT in the rheumatology outpatient clinic among FUO and IUO patients.Methods: Patients admitted to Prof. Dr. Cemil Taşcıoğlu City Hospital Internal Medicine Rheumatology Outpatient Clinic between February 2022 and September 2023 with FUO and/or IUO and for whom PET/CT scan was performed were included. Initial acute phase reactants, PET/CT results, definite diagnosis and follow-up of patients without a definite diagnosis were retrospectively evaluated.Results: Thirty patients were included. Fifteen patients received a final diagnosis. Diagnoses were ankylosing spondylitis (n=4), rheumatoid arthritis (n=1), systemic lupus erythematosus (n=3), giant cell arteritis (n=1), adult onset Still disease (n=1), undifferentiated connective tissue disease (n=1), undifferentiated vasculitis (n=1) and crystal arthropathy (n=1), Hodgkin lymphoma (n=1) and cryptococcosis (n=1). PET/CT’s diagnostic accuracy was 66.7%, sensitivity was 100% but specificity was 33%. In 15 patients a definite diagnosis was not reached but in most of these patients, fever did not recur and acute phase reactants regressed either spontaneously or with empiric treatment.Discussion: PET/CT reliably helps 50% FUO/IUO patients in receiving definite diagnosis. PET/CT’s high sensitivity implies that negative results can reliably exclude malignancies in most cases. However, due to its low specificity, positive test may not always imply a serious underlying condition. Majority of the definite diagnoses were rheumatic diseases with a very low proportion of infections and malignancies. This is mainly due to the detailed initial evaluations that are performed in internal medicine clinics. Future studies with more patients will better define the role of PET/CT in FUO/IUO patients in rheumatology clinics.Keywords: fever of unknown origin, inflammation of unknown origin, PET/CT, rheumatology